PENGARUH MUSIK KLASIK MOZART K.448 TERHADAP PENURUNAN TINGKAT KECEMASAN PADA MAHASISWA FAKULTAS KEDOKTERAN UPN VETERAN JAKARTA - Bunga Vidya Prajnanta (2022)
Anxiety is the most common mental disorder. Medical students have a higher level of anxiety than the general population due to their high academic load, physical burden, and mental burden. One way to reduce anxiety is to listen to classical music. This study aims to determine the effect of Mozart K.448 classical music on decreasing the anxiety level of medical students. This is a quasi-experimental study with a pretest-posttest control group design. Using purposive sampling with 35 preclinical students of the Faculty of Medicine UPN Veteran Jakarta, subjects were divided into an experimental group and a control group. The data was collected using the State-Trait Anxiety Inventory (STAI) to measure the level of anxiety before and after being given the Mozart K.448 classical music intervention for 3 days. The difference in pretest-posttest mean scores decreased by 10.94 for A-State and 7.88 for A-Trait. The results of the Paired T-Test showed a significant decrease in A-State (p=.000) and A-Trait (p=.000). The results of the Independent T-Test for A-Trait (p=.000) and Mann-Whitney U Test for A-State (p=.000) showed a difference between the experimental group and the control group. Mozart K.448 music effectively reduces the anxiety level of medical students in Faculty of Medicine UPN Veteran Jakarta.